Chapter 1 Producer Organisations as Twenty-First Century Farmer Institutions - Prasad, Shambu (Taylor & Francis, 2023)
Producer Organisations (POs) have the potential to provide alternatives to the current iniquitous economic systems through collectivising small farmers into economic production chains, and as essential actors in bringing about socially-oriented innovation. The exponential growth of Farmer Producer Organisations (FPOs) in India indicates ongoing efforts to transform farming as an enterprise through greater connection with markets and value chains, and lesser state involvement. The chapter provides a comprehensive review of global literature on collective enterprises and locates this research in the context of dynamic and fluid realities of the Global South that often get underrepresented in mainstream literature. The incubation, promotion and management of these institutions require a new inclusive frame to make sense of the complexity of FPOs in India beyond the narrow parameters of agricultural economics with a greater focus on socio-political dimensions. Through detailed studies of fifteen FPO cases, this volume seeks to expand the boundaries of the current discourse by exploring the multiple dimensions of FPO growth, management, and performance in diverse settings through a unique participatory research process.